Navigating Generational Transitions: Leadership Succession and Sustainability in Family Businesses - Kurniawan, Daniel (MES Bogor, 2024)
This study delves into the multifaceted dynamics influencing leadership succession and sustainability in family businesses, focusing on key variables such as intergenerational cooperation, family relationships, intrinsic motivation of successors, the controlling generation, and the presence of good governance. Employing a comprehensive literature review methodology, relevant academic sources were analyzed to construct a conceptual model that synthesizes theoretical and empirical insights. The findings highlight the essential role of strong intergenerational collaboration and robust governance structures in promoting smooth succession and long-term business viability. However, inherent challenges such as generational conflicts and lack of formalized succession plans pose risks to continuity. This study contributes a framework that underscores the importance of balancing familial values with strategic business objectives to sustain family firms across generations.